Harnessing Natures Palette: Bioengineering Yeast for Sustainable Textile Dyeing with Betalains - Ruhme, Bridget; Treml, Jack; Logan, Randall (Midwestern Journal of Undergraduate Sciences, 2024)
The fast-paced digital era has sparked an alarming surge of micro-trends in the fashion industry. Many companies prioritize mass production of textiles to fuel a culture of disposable fashion. This mass production of dyed textiles relies heavily on the use of synthetic azo dyes and, in some processes, the use of heavy metals such as lead, mercury, and chromium VI. Consequently, our planet’s landfills are inundated with an overwhelming volume of clothes that can leach toxic or carcinogenic chemicals into the environment. In response, scientists are researching sustainable alternatives that can harness living organisms to produce biosynthetic dyes that have less environmental impact. To contribute to this research effort, I aimed to develop a bioengineered strain of yeast that expresses red pigments called Betalains, a gene derived from beetroots. To achieve this, I will use a plasmid called UBQ: RUBY which is a gene cassette that contains requisite enzymes and promotors to express Betalains in a yeasts model. The expressed biosynthetic dye will then be purified and its fabric-standing properties will be characterized. Ultimately, this bioengineered yeast strain can be used to mass produce the red biosynthetic dye, Betalains, which could replace environmentally harmful synthetic dyes. This research project serves as a proof-of-concept study that could lay the foundation for the broader adoption of more sustainable and ethically conscious textile dyeing processes for decades to come.